Cover Feature: Synechococcus and Other Bloom‐Forming Cyanobacteria Exhibit Unique Redox Signatures (ChemElectroChem 2/2021). Issue 2 (23rd December 2020) - Tokunou, Yoshihide; Vieira Lemos, Rita; Tsujimura, Seiya; Okamoto, Akihiro; Ledezma, Pablo; Freguia, Stefano
Abstract : The Cover Feature shows that different species of cyanobacteria are blooming in a water body exposed to light, and a cyclic voltammogram provides an electrochemical signature for the presence of the cyanobacteria. More information can be found in the Communication by Y. Tokunou et al .